2013
DOI: 10.1159/000345437
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation of Epithelial Integrity in the Proximal Colon of Pigs

Abstract: Background: Within the gut, acetylcholine (ACh) is synthesised by enteric neurons, as well as by ‘non-neuronal' epithelial cells. In studies of non-intestinal epithelia, ACh was involved in the generation of an intact epithelial barrier. In the present study, primary cultured porcine colonocytes were used to determine whether treatment with exogenous ACh or expression of endogenous epithelium-derived ACh may modulate epithelial tightness in the gastrointestinal tract. Methods: Piglet colonocytes were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…Extended Life Span of PoCo83-3 Achieved by SV40 TAg Transduction As previously described, primary isolated pCECs generally entered a state of growth arrest after only a few passages of subcultivation [Petto et al, 2011;Lesko et al, 2013], a presumed consequence of cellular senescence [Campisi and Di d'Adda Fagagna, 2007]. In this study, pCECs were successfully transduced using a retroviral vector as confirmed by the stable expression of the SV40 TAg at the mRNA and protein levels ( Fig.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Extended Life Span of PoCo83-3 Achieved by SV40 TAg Transduction As previously described, primary isolated pCECs generally entered a state of growth arrest after only a few passages of subcultivation [Petto et al, 2011;Lesko et al, 2013], a presumed consequence of cellular senescence [Campisi and Di d'Adda Fagagna, 2007]. In this study, pCECs were successfully transduced using a retroviral vector as confirmed by the stable expression of the SV40 TAg at the mRNA and protein levels ( Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, some work groups used a combination of SV40 TAg and hTERT to generate immortalized cell lines [Matsumura et al, 2004;Desmarets et al, 2013;Olyslaegers et al, 2013]. In previous studies using primary pCECs [Petto et al, 2011;Lesko et al, 2013], these cells seemed to be quite sensitive when subjected to cell culture, usually maintaining active proliferation for only a few passages (according to our own unpublished observations). Regarding the sensitivity of the cells, the use of SV40 provides some advantages.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations